A pictorial illustration of conventional cryptography - Knudsen, Lars Ramkilde (DAIMI Report Series, 1994)
In this paper we consider conventional cryptosystems. We illustrate the differences between substitution, transposition and product ciphers by showing encryptions of a highly redundant cleartext, a portrait. Also it is pictorially demonstrated that no conventional cryptosystem in its basic mode provides sufficient security for redundant cleartexts.